The Effects of Sonic Logo and Visual Logo Repetition Towards Brand Recall, Recognition, Attitude, and Purchase Intention - Louise Valencia Pramana; Naomi Valerisha Astridira Putri; Fathony Rahman; Prita Prasetya (Journal of Consumer Sciences, 2024)
Most Indonesian e-commerce brands use sensory marketing, such as repetition of sonic logos and visual logos, in their advertisements. This research investigates the impact of repeated exposure to sonic logo and visual logos in advertisements on brand recall, brand recognition, attitudes toward the brand, and purchase intention. This study employed an experimental design with three repetition levels: one, three, and seven repetitions. The sample comprises individuals from the target market of Indonesian e-commerce platforms, selected through probability random sampling. The total sample is 300, with 100 participants in each group. The hypotheses were tested using one-way analysis of variance (ANOVA) to determine the significance of differences between groups. The results indicate that the repetition of sonic logo and visual logos in advertisements significantly enhances brand recall and recognition, positively influences attitudes toward the brand, and increases purchase intention. Industry players are advised to use sonic logos and visual logo repetition considering its significant effect on a brand. The recommended number of repetitions is three times to assess the effect of changes in the brand. Although additional repetitions beyond three may further enhance these effects, the incremental benefit diminishes.